Mahogany Webworm, Macalla thyrsisalis Walker (Insecta: Lepidoptera: Pyralidae: Epipaschilinae) - Forrest W. Howard; Sergio Gallo; Bryan Steinberg (EDIS)
EENY-383, a 5-page fact sheet by F. W. Howard, Sergio Gallo and Bryan Steinberg, is included in the Featured Creatures series. It describes this strikingly colored caterpillar pest of West Indies mahogany, its distribution, description, biology, host plants, damage and economic importance, management, and selected references. Published by the UF Department of Entomology and Nematology, July 2006.